Pogodbe o prodaji blaga in pogodbe o opravljanju storitev z vidika mednarodne pristojnosti v pogodbenih zadevah - Grum Trošt, Tina (Podjetje in delo, 2014)
The author discusses application of the rules on international jurisdiction in contractual matters. Due to the growing European market and thus a large number of cross-border legal relationships between natural and legal persons in the EU, in the future it can be expected that Slovenian courts will be faced with a growing number of disputes with an international element. The courts will first have to determine whether they have jurisdiction over the dispute, whereby they can also be met with the question of the definition of the disputed legal relationship as a contract for the sale of goods or a contract for the provision of services.
Keywords: pogodbe; pristojnosti; prodaja; reševanje; sodišča; spori